The Increasing Performance of School Principal Through Remuneration, Personality, and Job Satisfaction - Virgana (IJHCM (International Journal of Human Capital Management), 2018)
This research aims to know the influence of remuneration, personality, and job satisfaction on performance school principal, both directly and indirectly. Research using path analysis, a sample of randomly selected as many as 65 principal of elementary schools are civil servants in South Jakarta. The path analysis was done with some tests namely: Test of Normality of Error; Homogeneity Test; and significance and linearity test of regression coefficient. The results of the analysis found that there are: 1) direct influence of remuneration towards job satisfaction; 2) direct influence personality towards job satisfaction; 3) direct influence of regional allowances toward performance of principal; 4) direct influence of personality toward performance of principal; 5) direct influence job satisfaction toward performance of principal; 6) indirect influences of remuneration toward performance through job satisfaction; and 7) the indirect influence of personality toward performance of principal through job satisfaction. Therefore the variation improvements of principal performance are influenced by variation of the variable remuneration, personality, and job satisfaction